Pharmacological activation of the C5a receptor leads to stimulation of the β-adrenergic receptor and alleviates cognitive impairment in a murine model of familial Alzheimer’s disease - Fella, Eleni; Papacharalambous, Revekka; Kynigopoulos, Demos; Ioannou, Maria; Derua, Rita; Christodoulou, Christiana; Stylianou, Myrto; Karaiskos, Christos; Kagiava, Alexia; Petroula, Gerasimou; Pierides, Chryso; Kyriakou, Maria; et al. (Frontiers in Immunology, 2022)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease of the brain causing either familial or sporadic dementia. We have previously administered the modified C5a receptor agonist (EP67) for a short period to a transgenic mouse model of AD (5XFAD) and have observed not only reduction in beta-amyloid deposition and gliosis but also improvement in cognitive impairment. Inquiring however on the effects of EP67 in an already heavily burdened animal, thus representing a more realistic scenario, we treated 6 months old 5XFAD mice for a period of 14 weeks. We recorded a significant decrease in both fibrillar and pre-fibrillar beta-amyloid as well as tremendous amelioration of cognitive impairment. Following proteomic analysis and pathway association we postulate these events are triggered through the upregulation of beta-adrenergic and GABAergic signalling. In summary, our results reveal how inflammatory responses can be employed in inducing tangible phenotype improvements even in advanced stages of AD.